Autonomous Van and Robot Last-Mile Logistics Platform: A Reference Architecture and Proof of Concept Implementation - Marc Guerreiro Augusto; Julian Maas; Martin Kosch; Manuel Henke; Tobias Küster; Frank Straube; Sahin Albayrak (Logistics)
Background: With urban logistics facing challenges such as high delivery volumes and driver shortages, autonomous driving emerges as a promising solution. However, the integration of autonomous vans and robots into existing fulfillment processes and platforms remains largely unexplored. Method: This paper addresses this gap by developing and piloting a comprehensive blueprint architecture tailored for autonomous mobility in urban last-mile delivery. The proposed framework integrates autonomous vehicle operations, data processing, and stakeholder collaboration. Results: Through initial implementation and piloting, we demonstrate the practical applicability and advantages of this architecture. Conclusions: This study contributes to the understanding of essential data, services, and tools, providing a valuable guideline for Logistics Service Providers aiming to implement autonomous last-mile delivery solutions.